2011
DOI: 10.1038/eye.2011.185
|View full text |Cite
|
Sign up to set email alerts
|

Three horizontal muscle surgery for large-angle infantile esotropia: validation of a table of amounts of surgery

Abstract: Purpose To validate a table of amounts of three horizontal muscle surgery in patients with large-angle infantile esotropia (Z60 prism dioptres, PD). Methods A prospective interventional case series reporting the postoperative alignment of 51 patients (27 male, 24 female) over a 15-year period was conducted. Surgery amounts were according to a published table developed on a previous patient cohort (n ¼ 49), using bilateral medial rectus recession with graded unilateral lateral rectus resection. Kaplan-Meier lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
12
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 20 publications
3
12
0
2
Order By: Relevance
“…Our results agree with other authors [27,28] suggesting this approach in large angle esotropia, for the low rate of either residual esotropia or consecutive exotropia and the good long-term success rate.…”
Section: Discussionsupporting
confidence: 93%
“…Our results agree with other authors [27,28] suggesting this approach in large angle esotropia, for the low rate of either residual esotropia or consecutive exotropia and the good long-term success rate.…”
Section: Discussionsupporting
confidence: 93%
“…Techniques reported include augmented medial rectus recession to exceed the traditional 5 mm maximum recession, 5,31,32 simultaneous botulinum toxin A injection 33 and three-muscle surgery including bilateral medial rectus muscle recession and one lateral rectus muscle resection surgery. 3,34 After a long-term evaluation of post-operative motor outcomes in infantile esotropia, Maglia et al suggested a two-horizontal muscle approach in small-angle esotropias and a multiple-muscle surgery in large-angle esotropias. 35 Since many of our patients had large-angle esotropia, three-muscle surgery was frequently done.…”
Section: Discussionmentioning
confidence: 99%
“…We believe that synoptophore measurements may be more standardized, minimizing potential errors inherent in the use of prisms or Krimsky tests for large-angle strabismus in this age group. 10,[18][19][20] It has been suggested that the synoptophore may overestimate esotropic deviations owing to presumed induced proximal convergence. It could be hypothesized that this approach might have resulted in the overestimation of undercorrections.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Popular surgical options include large bilateral medial rectus muscle recessions [3][4][5] and selective surgery on 3 or even 4 extraocular muscles. [6][7][8][9][10] Alternative approaches include large unilateral medial rectus muscle recession and lateral rectus muscle resection or adding conjunctival recession, medial pulley fixation, or botulinum toxin treatment to the medial rectus muscle recession. [11][12][13] Many strabismologists would opt for large bilateral medial rectus muscle recessions because this is a simple symmetrical approach, involves a shorter operating time, and leaves the lateral rectus muscles untouched for subsequent surgery, if needed.…”
mentioning
confidence: 99%
See 1 more Smart Citation